A novel sintering method for polycrystalline NiMnGa production for elastocaloric applications - Francesca Villa; Elena Villa; Enrico Bassani; Corrado Tomasi; Francesca Passaretti; Riccardo Casati (Journal of Materials Research and Technology, 2024)
NiMnGa Heusler alloy plays a key role as reference system for ferromagnetic shape memory alloys (FeSMAs) and their peculiar functional properties including large magnetic-field-induced strain, magnetocaloric and elastocaloric effects. Moreover, the microstructure of polycrystalline NiMnGa alloys has been investigated and optimized to improve the mechanical properties and to reduce their typical brittleness. For this reason, increasing interest has been devoted to different kinds of fabrication routes for this alloy, such as powder metallurgy processes. In the present study, a polycrystalline Ni50Mn30Ga20 (atomic %) alloy is produced by means of an unconventional sintering method that involves the canning of powders and the subsequent processing by hot rolling. This process was implemented according to the results obtained by means of the open die pressing (ODP) sintering of NiMnGa which was investigated in a previous work. The present study is aimed at developing an alternative and cost-effective sintering method for the consolidation of fully-dense NiMnGa samples. The process allowed reducing the intrinsic brittleness of the alloy. A heat treatment at 925 °C for 6 h was applied and allowed achieving a maximum adiabatic ΔT of +6.3 °C and - 4.5 °C with a strain of 4 % and a strain rate of 400 %/min in compression. The novel method led to very promising elastocaloric properties, making NiMnGa a suitable candidate for solid-state cooling and heating applications.